Estimation of Alpha-L-Fucose and Vitamin D3 Levels in Beta Thalassemia Patients in Al-Najaf Province - Mohammed Abdulrazzaq Assi (Journal of Global Pharma Technology, 2016)
The present study deals with the prominent inherited disease that is thalassemia. Β-thalassemia is an extreme hereditary blood disorder resulted after a change in the gene encoding for the hemoglobin β chains. Hemoglobin is made up of a genetic defect in the synthesis of a globin chain, or more, which results in a reduced rate of these chains. The creation of atypical hemoglobin molecules is a result of the reduction in the synthesis of one chain of the globin, and thus, leads to the most specific symptom of the thalassemia; anemia. This study was conducted with 40 subjects, whose age ranges from 4-20 years, divided among (males 30 and females10), who has visited the Thalassemia Center at Al-Zahraa Teaching Hospital in Najaf province, Iraq, for managing the disease, and 40 voluntary healthy as a control group. The study has been done between September and February 2019. This study was performed to evaluate the levels of serum of Vitamin D3 and L-Fucose in major and intermediate beta-thalassemia patients. It also estimates protein-bound fucose (PBF), hemoglobin (Hb), hematocrit (HCT), liver function tests, calcium, TIBC and Ferritin. The results showed a significant increase in the levels of alpha -L- fucose and protein-bound fucose in thalassemia patients as compared with control. The results showed a very important reduction (P<0.001) in Vitamin D3,Hb, HCT, TIBC and calcium in thalassemia patients in both males and females in comparison with the healthy control, except ferritin, AST,and ALT which is increased significantly(p<0.001) in those patients in comparison with control. Keywords: Thalassemia, Vitamin D, L-Fucose.